Hellenistic Rationality and the Formation of Sunni Legal Epistemology (800–1100 CE): A Postcolonial Methodological Inquiry - Sumarjoko, Sumarjoko; Karim, Mohammad Abdul; Hak, Nurul (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
This study argues that the formation of Sunni Islamic legal epistemology between the eighth and eleventh centuries CE cannot be adequately understood as a passive reception of Greco-Hellenistic rational traditions. Instead, it emerged through a complex process of internal methodological negotiation within the Islamic intellectual tradition. Rather than wholesale adoption of Aristotelian or Neoplatonic modes of reasoning, Muslim jurists selectively appropriated and critically reconfigured rational tools within the normative and epistemic framework of uṣūl al-fiqh, thereby generating a distinct form of legal rationality grounded in revelation, linguistic analysis, and juristic practice. Employing a postcolonial methodological inquiry, this study challenges earlier Orientalist interpretations that reduced Islamic jurisprudence to Roman or Hellenistic precedents, arguing that such accounts overlook the autonomy and internal dynamics of Islamic legal thought. The findings highlight the active epistemic agency of Muslim scholars who, through concepts such as qiyās and ʿillah, constructed a coherent system of legal reasoning while negotiating sociopolitical contexts, textual authority, and intellectual power structures. This study concludes that Sunni legal rationality developed through creative transformation rather than derivative reception, reaffirming the methodological autonomy and intellectual originality of Islamic law within the broader history of global legal traditions.